Strengthening the Islamic Religious Education Curriculum to Answer the Challenges of Character Education in the Era of Globalization - Nur Fadilah Ikhwany Pulungan; Juliani; Hilal Fatra; Nurmala Sari; Isma Pratiwi (Journal of Contemporary Islamic Primary Education, 2023)
The Islamic Religious Education (PAI) curriculum plays a crucial role in shaping students' character and morals, as well as instilling religious values that can be applied in everyday life. However, the challenges of globalization, which are transforming social, cultural, and technological patterns, require adjustments to the PAI curriculum to stay aligned with the times. This study aims to explore the importance of developing a relevant PAI curriculum in the era of globalization and to identify concrete steps in adapting the curriculum to the needs of students and global challenges. This research uses a qualitative approach with literature review and interviews with curriculum developers, PAI teachers, and academics. The findings of the study indicate that the development of a relevant PAI curriculum should cover three main aspects: integrating Islamic values with advancements in science and technology, enhancing students' social skills and character, and utilizing media and technology in the learning process. This study also emphasizes the importance of collaboration between the government, and educational institutions.